Safety syringe - Abu Talib, Abd. Rahim; Basri, Adi Azriff; Mohd Zabidi, Siti Zuraifah; Yahaya, Mohd Salleh; Mat Isa, Khairi (2011)
The present invention relates to a safety syringe (100) having a hollow barrel (1), plunger (2) and a detachable needle support (4), characterized in that the safety syringe (100) includes; a) a piston gasket (3) interference fit with the plunger head (7) of the plunger (2); b) a plurality of bone structures (6) provided at the barrel head (1a) of the hollow barrel (1) to temporarily engage and support the needle support (4); c) a plurality of slots (8) longitudinally disposed at one substantial distal end of the needle support (4); and d) stoppers (5) provided at the barrel head (1a); wherein a fluid is injected by a first stroke of the plunger (2) under normal load; and an additional load is applied to the plunger (2) to compress the piston gasket (3) so that the plunger head (7) of the plunger (2) travels further to break the bone structures (6) for subsequent retraction of the needle support (4) on a second stroke.